Synthesis and characterization of UV-curable vinyl ether functionalized urethane oligomers - (:unkn) unknown (ELSEVIER SCIENCE SA, 2004)
Vinyl ether functional group bearing urethane-based oligomers were synthesized by reacting toluene (2,4-2,6) diisocyanate (TDI) with 4-hydroxybutyl vinyl ether (HBVE) and three different diols, namely poly(ethylene glycol), poly(propylene glycol) and alpha-omega-hydroxy terminated organofunctional poly(dimethyl siloxane). The structures of the oligomers were characterized by FTIR. All resins, except the poly(ethylene glycol) containing one, were successfully polymerized cationically by UV irradiation in the presence of a diaryliodonium photoinitiator and isopropyl thioxanthone (ITX) photosensitizer. Physical properties of UV-cured films such as gel content, solvent resistance, stress-strain and water absorption behaviors, were examined. The stress-strain tests showed that PDMS containing oligomer gives better tensile strength and elongation values when compared with PPG containing one. The curing process was followed quantitatively by monitoring the disappearance of vinyl ether groups by real-time infrared spectroscopy. The reactivity of PDMS containing oligomer was found higher than PPG containing one. In addition, thermal gravimetric analysis of PDMS containing polymeric films gave higher char yield due to their silicone containing structure. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: UV-curing; vinyl ethers; cationic polymerization; poly(dimethyl siloxane); kinetics; IR spectroscopy; STRUCTURE-PROPERTY RELATIONSHIPS; POLYMERIZATION